78.7k views
2 votes
Simplify the expression.
2(3n+4)-2(2n+5)

1 Answer

5 votes
First, use the distributive property.
2 • 3n = 6n
2 • 4 = 8
-2 • 2n = -4n
-2 • 5 = -10
This makes the expression 6n + 8 - 4n - 10.
Now combine like terms.
The terms are:
6n
8
-4n
-10
The like terms are:
6n and -4n
8 and -10
So by combining like terms, we can simplify the expression to 2n -2.
This is as far as you can simplify, so it is the correct answer.

Answer:
2n - 2

Hope this helps!
User Infojunkie
by
5.4k points